Assessing the damage control resuscitation: Development, drivers and direction. (28th August 2015) - Quinn, David; Frith, Daniel
Abstract Damage control resuscitation (DCR) has become a more widely adopted acute management strategy over the past decade. A cornerstone of this strategy is the performance of an initial limited surgical intervention for the control of active bleeding and contamination. This technique is indicated where significant physiological compromise exists and immediate surgical intervention is required. This damage control surgery itself is completed judiciously to allow a period of resuscitative stabilisation before later definitive surgical solutions. This discussion describes the three further principles of DCR and then explores the rationale and drivers behind the development of this approach.